2001
DOI: 10.1083/jcb.153.4.823
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role for the Armadillo Protein Plakoglobin in the Autoimmune Disease Pemphigus Vulgaris

Abstract: In pemphigus vulgaris (PV), autoantibody binding to desmoglein (Dsg) 3 induces loss of intercellular adhesion in skin and mucous membranes. Two hypotheses are currently favored to explain the underlying molecular mechanisms: (a) disruption of adhesion through steric hindrance, and (b) interference of desmosomal cadherin-bound antibody with intracellular events, which we speculated to involve plakoglobin. To investigate the second hypothesis we established keratinocyte cultures from plakoglobin knockout (PG−/−)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
177
3
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(202 citation statements)
references
References 56 publications
18
177
3
4
Order By: Relevance
“…Keratinocytes from plakoglobin knock-out mice form desmosome-like structures that appear to mediate cell-cell adhesion in monolayer cultures but are resistant to PV IgG-mediated keratin filament retraction (11). This observation suggests that mechanisms in addition to steric hindrance may be required for PV IgG to mediate the loss of keratinocyte cell-cell adhesion and provides additional support for the hypothesis that signaling plays a role.…”
Section: Figsupporting
confidence: 61%
See 1 more Smart Citation
“…Keratinocytes from plakoglobin knock-out mice form desmosome-like structures that appear to mediate cell-cell adhesion in monolayer cultures but are resistant to PV IgG-mediated keratin filament retraction (11). This observation suggests that mechanisms in addition to steric hindrance may be required for PV IgG to mediate the loss of keratinocyte cell-cell adhesion and provides additional support for the hypothesis that signaling plays a role.…”
Section: Figsupporting
confidence: 61%
“…Proposed mechanisms for PV IgG-induced keratinocyte detachment include (a) proteinase activation, (b) steric hindrance, and (c) activation of transmembrane signaling that down-regulates cell-cell adhesion (7)(8)(9)(10)(11). Previous work has suggested that PV IgG may activate intracellular signaling events; however, the precise nature and biological consequences of these events and their relationship to the mechanism of PV IgG-induced acantholysis remain unknown (7,8).…”
mentioning
confidence: 99%
“…The average areas were compared by using Student's t test. Previous studies (5) demonstrated that loss of PG expression caused severe skin fragility in PG knockout mice and decreased adhesion in keratinocytes established from the skin of these mice (8). Despite the lack of PG in PGϪ͞Ϫ cells, the protein level and cellular localization of the closely related ␤-catenin were comparable in keratinocyte cultures established from the skin of PG knockout mice (PGϪ͞Ϫ) and heterozygote control mice (PGϩ͞Ϫ) (Fig.…”
mentioning
confidence: 92%
“…PG's critical role in maintaining tissue integrity is underscored by skin and heart dysfunction in PG-null mice and patients with pathogenic homozygous mutations (4)(5)(6)(7). In addition, keratinocyte cultures established from PG-null mice exhibit reduced adhesion in a mechanical dissociation assay (8).…”
mentioning
confidence: 99%
“…Dispase-based Keratinocyte Dissociation Assay-The assay was performed as described in the literature with the following modifications (17,18). HaCaT cells were seeded on 12-well plates and grown to confluence.…”
Section: Methodsmentioning
confidence: 99%